The cultural tradition as a factor of sustainable development in an era of global instability - Kolyadko, Ilya N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the conceptual analysis of the phenomenon of cultural traditions in the modern unstable societies. The thesis according to which cultural tradition is a form of social stability and certainty, society structures, provides translation and reproduction of values, constitutes and supports social order. In the context of global instability tradition serves as a value-regulatory system of coordinates to the sustainable development of modernizing societies.